Work out of office: how and when does employees’ self-control influence their remote work effectiveness? - Qi, Lei; Xu, Yuping; Liu, Bing (Frontiers in Psychology, 2023)
Introduction The purpose of this study is to understand the positive effects of employees’ self-control on their self-efficacy and work effectiveness in the context of remote work, as well as social support (organizational support, interaction with supervisors, and family support) moderating role on such positive effects. Methods Based on social cognitive theory, this study collects two-phase data with a sample of 240 remote workers. Results The results show that employees’ self-control positively influences their remote work self-efficacy, which in turn positively increases their remote work effectiveness. Moreover, perceived organizational support, interaction with supervisors, and family support strengthen the effect of self-control on remote work self-efficacy. Discussion First, this study explores the mechanism of self-control on remote work effectiveness, highlights the importance of self-control in remote work, and provides guidance for employees to improve remote work effectiveness. Second, this study discusses the mediating role of remote work self-efficacy between self-control and remote work effectiveness and reveals the psychological mechanism of employees’ self-control in remote work. Finally, this study comprehensively considers three types of support from work and family and analyzes the interaction between internal control and external support on remote work self-efficacy, which provides suggestions for enhancing employees’ confidence in remote work.